Role of Religiousness/Spirituality in Resilience of Fisheries College Cadets - Rahmawati, Sri (Journal of Educational, Health and Community Psychology, 2014)
AbstractÂ Experts agree that resilience involves internal factors and external factors. In addition to those two factors, religious beliefs, spirituality and the capacity to give a meaning to the traumatic event, it is also discussed as a factor involved in the development of resilience. A number of researchers explore their findings to see the relationships between religiousness/ spirituality and resilience. People experiencing emptiness of spiritual, increasingly awareness of the importance of the involvement of religion/spiritual in solving problems, but itâs increasingly depletion due to exposure to materialistic life.This researchÂ is conducted to see the influence of religiousness/spirituality on resilience occuring among college students. The results showed that the following dimensions are related to the increasing resilience of a person: daily experience of human spiritual, beliefs/values, willingness to forgive, and the worship of religious activities as well as evaluating a persons level of religiousness. Discussion and implication of the research results are included.Â Keyword: Religious coping; Resilience; Cadets of STP; Quantitative ResearchÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â